THE MACROZOOBENTHOS COMMUNITY STRUCTURE AT SITU CIBEUREUM, SOUTH TAMBUN DISTRICT, BEKASI REGENCY, WEST JAVA PROVINCE - Wahyudi, Rifki; Hasan, Zahidah; Grandiosa, Roffi; Arief, Mochamad Candra W. (Jurusan Perikanan dan Kelautan, 2024)
Human and industrial activities increase the amount of waste or pollutants in water, damaging the environment. Macrozoobenthos can be used as bioindicators of water quality. This study aimed to determine the water quality at Situ Cibeureum using chemical, physical, and biological parameters. Using a purposive sampling method, samples were taken four times at 14-day intervals from four station points. The results indicated that Situ Cibeureum was moderately polluted, with the highest abundance of macrozoobenthos found in the species Filopaludina javanica, moderate diversity of macrozoobenthos, a high uniformity index, and low dominance. The FBI value at Situ Cibeureum indicated slightly poor to fair water quality, with values ranging from 5.40 to 6.20. The average water temperature was 29.7℃-30.6℃. The average turbidity was 22.37-39.04 NTU. The average BOD value was 8.5-10.5 mg/l. The dissolved oxygen concentration ranged from 5.6 to 7.6 mg/l. The lowest average pH value was 6.7 at station 2. The pH value of the substrate ranged from 6.5 to 7.5. The C-organic content was 2.89-4.42%. The N-total concentration ranged from 0.21 to 0.53%. The macrozoobenthic species found during the research were Filopaludina javanica, Pomacea canaliculata, Melanoides tuberculata, Pilsbryconcha exilis, and Thiara scabra. Keywords: Bioindicator, C-organic, Filopaludina javanica, purposive sampling.